2004
DOI: 10.1002/chir.20058
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselectivity in formation of oxacephams from 1,3‐alkylidene‐threitols

Abstract: The [2+2]cycloaddition of CSI to the (Z)-propenyl ethers derived from respective 1,3-methylidene- and 1,3-ethylidene-threitols, contrary to the corresponding erythritol derivatives, is characterized by a low stereoselectivity and a lack of stereospecificity. On the other hand, the alternative method of the oxacepham formation, based on the 4-vinyloxy-azetidinone, proceeds with an excellent stereoselectivity. The CD-spectroscopy offers an attractive tool for determination of the absolute configuration of the br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The (1R,3ЈR,4ЈR) configuration assigned for 26 and the ratio of 24 : 25 : 26 at Ϫ50°C indicated that the adduct 24 underwent epimerization at the stage of the N-chlorosulfonylated [2ϩ2]cycloadduct. Similar epimerization has also been noticed in the past [25].…”
Section: Synthesissupporting
confidence: 84%
“…The (1R,3ЈR,4ЈR) configuration assigned for 26 and the ratio of 24 : 25 : 26 at Ϫ50°C indicated that the adduct 24 underwent epimerization at the stage of the N-chlorosulfonylated [2ϩ2]cycloadduct. Similar epimerization has also been noticed in the past [25].…”
Section: Synthesissupporting
confidence: 84%
“…In the case of threitols 19 and 20 the stereoselectivity of the formation of β-lactams 37, 38 and 39, 40 was much less satisfactory and amounted to 1:1 and 1.4:1, respectively. In comparison with the corresponding vinyl ethers 62 [15] and 63, [16] the cycloadditions giving alkoxyallenes 9, 10 and 19, 20 proceeded with a significantly lower stereoselectivity in both the erythritol and threitol series.…”
Section: Synthesis Of Alkoxyallenes Cycloaddition and Formation Of Cmentioning
confidence: 93%